The contribution of professors of Hygiene to the progress and development of public health in Italy: one hundred years of history - Signorelli, Carlo; Squeri, Raffaele; Picerno, Isa Anna Maria; Di Pietro, Angela; Delia, Santi Antonino; Grillo, Orazio Claudio; Sciacca, Salvatore; Fara, Gaetano Maria (Acta Biomedica Atenei Parmensis, 2019)
In 1917 Achille Sclavo, a distinguished researcher and founder of the Italian Society of Hygiene, ended up the first term as Rector of the University of Siena. Since then, the contribution of professors of hygiene in Italian universities has ranged over several relevant topics including vaccinations, environmental hygiene, hospital hygiene, healthcare organization and management, with an important contribution to the health reform of 1978 by Augusto Giovanardi and Alessandro Seppilli. Several Academic Schools (Roman, Neapolitan, Genoese, Sicilian, Venetian, Lombard, etc.) have produced excellent researchers, teachers and mentors who have also occupied important positions in the panorama of the Italian health system. This note analyzes the main research topics, the most famous institutes and departments of hygiene and public health and the contributions of the most famous professors for the development of the discipline, the management of the post- graduated Schools in hygiene and preventive medicine, the commitment in scientific associations and the role of some of them in important institutional positions. Even through its contribution and constant commitment to the institutions, Italian public health has achieved the reputation of being one of the best known and appreciated in the international scientific community.